Cognitive-Linguistic Interventions for Engineering Education: Visual Thinking Strategy Efficacy - Rai, Apurva; Dayal, Ashok (Journal of Research in Vocational Education, 2025)
Effective communication is crucial in the engineering field, yet many engineers struggle to articulate complex technical concepts. The Picture Perception Method (PPT) leverages visual stimuli to enhance cognitive and linguistic processes, promoting language fluency among engineers. This method involves interpreting and describing profession-related images, fostering critical thinking, cohesive storytelling, and precise technical vocabulary use. By stimulating cognitive flexibility, PPT improves oral and written communication, making it especially valuable in multilingual and global settings. With regular practice, engineers can effectively convey complex ideas, thereby enhancing their professional competence in diverse work environments.